An Overview of The Preparedness of Fishers about First Aid in Drowning (Water Rescue) at Labuhan Beach, Antiga Village - Ni Putu Juliantari (Green Publisher Indonesia, 2024)
Emergencies can happen to anyone, anytime and anywhere, while one of the emergencies that often occurs in the waters is drowning. A fisherman can experience drowning due to lack of preparation in going to sea. Deaths due to drowning can be prevented by providing first aid quickly and accurately. Drowning preparedness plays an important role in the anticipation and provision of first aid in the event of drowning. The purpose of this study was to determine the characteristics of fishermen and describe the preparedness of fishermen regarding first aid in the event of drowning (water rescue) on Labuhan beach, Antiga Village. This research is a descriptive study with an observational approach. The sampling technique used was purposive sampling in accordance with the inclusion and exclusion criteria, with a total of 67 respondents. Data collection was carried out by distributing questionnaires. The results showed that the characteristics of respondents had a bad drowning experience such as drowning, being hit by waves, falling off the boat, and being dragged by waves. The level of preparedness of the fishermen was in the ready category (52.2%), on four indicators of knowledge and attitude less ready (55.2%), emergency planning very ready (52.2%), disaster warning system less ready (46.3%), resource mobilization very ready (46.3%). The conclusion of this study is that the fishermen of Antiga Village consider that drowning deaths are common and drowning can occur to experienced fishermen.